Hot-pressed ceramic core and preparation method thereof
Through the preparation method of hot-pressed ceramic core, chopped fibers are used as pore-making and reinforced phases, the bending strength and porosity of the ceramic core are improved, and the problem of regulating the performance of ceramic core in the existing technology is solved, and the problem of regulating the performance of ceramic cores is realized. Preparation of high-performance ceramic cores.
Patent Information
- Application Number
- CN202310932619.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-07-27
AI Technical Summary
When the existing ceramic cores improve flexural strength and porosity, they have high manufacturing costs, limited adjustment range, and insufficient regulation accuracy, making it difficult to meet the complex structural needs of the cooling channel of the turbine blade of the aircraft engine.
Using the preparation method of hot-pressed ceramic core, pore-making reinforced particles are prepared by coating agent and pore-making reinforced agent, and mixed with the skeleton powder and plasticizer, and subjected to press-injection molding and degreasing sintering to introduce short-term The fiber cutting acts as a pore-making and reinforced phase to improve the porosity and bending strength of the core.
It significantly improves the open porosity and bending strength of the ceramic core, reduces cracks and defects during degreasing, improves the overall performance of the core, and meets the application needs of high temperature and high precision.
Smart Images

Figure CN116924815B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of investment casting, in particular to a hot-pressed ceramic core and a preparation method thereof. Background Art
[0002] Ceramic cores are key transition pieces for the preparation of hollow structural parts with complex structures using precision casting technology, and their performance directly determines the performance of complex structural alloy castings. The hollow turbine blades of aircraft engines are a typical application case of ceramic cores. With the development of manufacturing technology for high-temperature alloy turbine blades of aircraft engines, the temperature before the turbine of aircraft engines continues to rise, and the air film cooling technology of hollow blades has developed rapidly. The structure of ceramic cores used to prepare cooling channels for hollow blades in precision casting has become more complex, and the requirements for their dimensional accuracy and high-temperature performance have also continued to increase. Therefore, the research and development of new high-performance ceramic core products and new preparation processes is imminent.
[0003] The preparation of ceramic cores requires comprehensive consideration of the bending strength and open porosity of the ceramic cores. At present, the strength and porosity of ceramic cores for turbine blades are mainly comprehensively regulated through medium and low temperature strengthening, material formulation, and sintering process. However, the regulation accuracy is insufficient, the effect is poor, and the trial production cycle is long. Therefore, in order to ensure that the ceramic core has high bending strength while improving the open porosity of the core, it has become the primary issue in the research and development of materials and processes for complex structure ceramic cores. The methods currently used include: using methods such as particle size stacking model optimization, strengthening process optimization, and sintering system adjustment to improve the bending strength of the ceramic core while improving the open porosity of the core. However, the above methods generally have problems such as high manufacturing cost and limited adjustment range.
[0004] Therefore, in order to solve the above problems, it is necessary to develop a process and a matching raw material formula that can simultaneously improve the open porosity and bending strength of the ceramic core, so as to prepare a high-performance ceramic core. Summary of the invention
[0005] In view of this, the present invention provides a hot-pressed ceramic core and a preparation method thereof, the main purpose of which is to simultaneously improve the bending strength and open porosity of the ceramic core.
[0006] In order to achieve the above object, the present invention mainly provides the following technical solutions:
[0007] On the one hand, an embodiment of the present invention provides a method for preparing a hot-pressed ceramic core, which comprises the following steps:
[0008] The step of preparing pore-forming strengthening particles is as follows: using a coating agent and a pore-forming strengthening agent as raw materials to prepare pore-forming strengthening particles; wherein the pore-forming strengthening particles are in a core-shell structure with the coating agent as a shell layer and the pore-forming strengthening agent as a core layer; wherein the pore-forming strengthening agent is selected from chopped fibers, and the chopped fibers are one or a mixture of SiC fibers and carbon fibers;
[0009] The step of preparing hot-pressed ceramic core slurry is as follows: mixing a mixed powder and a plasticizer to obtain a hot-pressed ceramic core slurry; wherein the mixed powder comprises a skeleton powder, a filler, and the pore-forming strengthening particles;
[0010] Injection molding step: performing injection molding on the hot-pressed ceramic core slurry to obtain a hot-pressed ceramic core wet blank;
[0011] Degreasing and sintering steps: degreasing and sintering the hot-pressed ceramic core wet blank to obtain a hot-pressed ceramic core.
[0012] Preferably, in the step of preparing the pore-forming and reinforcing particles: the diameter of the chopped fibers is 0.1-0.2 μm and the length is 1-10 μm.
[0013] Preferably, the shell layer thickness of the pore-forming strengthening particles is 0.05-0.1 μm.
[0014] Preferably, in the step of preparing the pore-forming and strengthening particles, the coating agent is a mixture of 50-60% epoxy resin and 40-50% polysilicon carbide resin by volume. Preferably, the viscosity of the epoxy resin is 1-50cp and the molecular weight is 350-8000; preferably, the viscosity of the polysilicon carbide resin is 1-50cp and the molecular weight is 350-8000.
[0015] Preferably, in the step of preparing the pore-forming strengthening particles: after mixing the pore-forming strengthening agent and the coating agent, a first stirring treatment is performed at a temperature of 150-240° C., and after drying, pore-forming strengthening particles with a core-shell structure are obtained; preferably, the first stirring treatment time is 10-20 hours.
[0016] Preferably, in the step of preparing the hot-pressed ceramic core slurry: the step of preparing the mixed powder includes: mixing the skeleton powder, filler and pore-forming strengthening particles, and then performing a second stirring treatment to obtain a mixed powder; preferably, the time of the second stirring treatment is 2-3 hours.
[0017] Preferably, in the step of preparing the hot-pressed ceramic core slurry: after mixing the mixed powder and the plasticizer, a third stirring treatment is performed at a temperature of 80-120° C. to obtain the hot-pressed ceramic core slurry; preferably, the time of the third stirring treatment is 150-240 hours.
[0018] Preferably, in parts by weight, the raw materials for preparing the hot pressing ceramic core slurry include:
[0019] 60-80 parts by weight of skeleton powder;
[0020] Filler 5-15 parts by weight;
[0021] 5-15 parts by weight of pore-forming strengthening particles;
[0022] Plasticizer 10-20 parts by weight.
[0023] Preferably, the skeleton powder is one or both of Al2O3 and SiO2.
[0024] Preferably, the filler is one or more of ZrO2, Y2O3, and ZrSiO4.
[0025] Preferably, the particle size of the skeleton powder is 35-125 μm.
[0026] Preferably, the filler has a particle size of 5-55 nm.
[0027] Preferably, the plasticizer is a mixture of 70-80% paraffin and 20-30% beeswax by mass.
[0028] Preferably, in the injection molding step, the injection molding parameters are set as follows: the injection pressure is 2-4 MPa, and the pressure is maintained for 10-30 seconds.
[0029] Preferably, in the degreasing and sintering steps: in the degreasing treatment: the degreasing treatment temperature is 400-600°C, and the degreasing treatment time is 120-180min; preferably, the heating rate is 1-5°C / min, and the cooling rate is 1-5°C / min.
[0030] Preferably, in the sintering process: the sintering temperature is 1300-1500°C, and the sintering time is 180-300min; preferably, the heating rate is 2-8°C / min, and the cooling rate is 2-8°C / min.
[0031] On the other hand, an embodiment of the present invention further provides a hot-pressed ceramic core, wherein the hot-pressed ceramic core is prepared by any of the above-mentioned methods for preparing a hot-pressed ceramic core.
[0032] Compared with the prior art, the hot-pressed ceramic core and the preparation method thereof of the present invention have at least the following beneficial effects:
[0033] The embodiment of the present invention proposes a method for preparing a hot-pressed ceramic core, comprising the following steps: using a coating agent and a pore-forming reinforcing agent as raw materials to prepare pore-forming reinforcing particles; wherein the pore-forming reinforcing particles are in a core-shell structure with the coating agent as a shell and the pore-forming reinforcing agent as a core; wherein the pore-forming reinforcing agent is selected from chopped fibers, and the chopped fibers are a mixture of one or two of SiC fibers and carbon fibers; mixing the mixed powder and the plasticizer to obtain a hot-pressed ceramic core slurry; wherein the mixed powder includes a skeleton powder, a filler, and pore-forming reinforcing particles; performing injection molding on the hot-pressed ceramic core slurry to obtain a hot-pressed ceramic core wet blank; degreasing and sintering the hot-pressed ceramic core wet blank to obtain a hot-pressed ceramic core. It should be noted about the above preparation steps that: the present invention introduces pore-forming reinforcing particles into the raw materials for preparing the hot-pressed ceramic core slurry for the first time, and the main component of the pore-forming reinforcing particles is chopped fibers. Here, the embodiment of the present invention introduces chopped fibers as pore-forming and reinforcing phases into the ceramic core, and improves the core open porosity through the supporting effect of the fibers on the matrix powder (on the one hand, the addition of chopped fibers, since the fibers are messy, pores will be formed between the fibers due to the intersection of the fibers; on the other hand, the amount of fiber addition is controlled so that the fibers come into contact to form a supporting effect; the above two aspects achieve an increase in open porosity), and at the same time, the bridging effect of the fibers is used to improve the bending strength of the core. Further, the pore-forming and reinforcing particles are a core-shell structure with chopped fibers as the core and a coating agent as the shell. Here, the present invention coats the surface of the chopped fibers before adding them, which can significantly improve the uniformity of the chopped fibers in the core slurry. At the same time, the coated surface layer can sinter and react with the matrix powder of the core during the core sintering process, promoting the improvement of the core bending strength while inhibiting the carbonization of the fibers during the sintering process. In addition, the short-cut fibers added in the present invention can provide a channel for the overflow of the plasticizer during the degreasing process, promote the decomposition of the plasticizer, improve the degreasing efficiency of the core, and reduce the cracks and defects of the core caused by degreasing. In summary, the above method of the present invention can prepare a hot-pressed ceramic core with high open porosity, high strength, and strong crack propagation resistance.
[0034] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a process flow chart of a method for preparing a hot-pressed ceramic core provided by an embodiment of the present invention;
[0036] Figure 2 is a diagram of the internal microstructure of the hot-pressed ceramic core prepared in Example 1;
[0037] Figure 3 Schematic diagram of the structure of the pore-forming and strengthening particles prepared in Example 1. DETAILED DESCRIPTION
[0038] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" do not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0039] The present invention is aimed at the hot-pressing ceramic core preparation technology and designs for the first time a core material formula doped with a high content of surface-modified fibers (i.e., a shell layer is coated on the surface of the fiber), and utilizes the supporting effect of the fibers on the matrix ceramic to increase the open porosity of the ceramic core (it should be noted that: on the one hand, by adding chopped fibers, since the fibers are messy, pores will be formed between the fibers due to the crossing of the fibers; on the other hand, the amount of fiber addition is controlled so that the fibers come into contact with each other to form a supporting effect; the above two aspects achieve the improvement of the open porosity), and at the same time utilizes the mechanisms of bridging and blocking cracks by the fibers to increase the bending strength of the core, thereby achieving the simultaneous improvement of the bending strength and open porosity of the ceramic core.
[0040] The main scheme of the present invention is as follows:
[0041] The present invention provides a method for preparing a hot-pressed ceramic core. Figure 1 As shown, it includes the following steps:
[0042] The steps of preparing pore-forming strengthening particles are as follows: using a coating agent and a pore-forming strengthening agent as raw materials to prepare pore-forming strengthening particles; wherein the pore-forming strengthening particles are in a core-shell structure with the coating agent as a shell layer and the pore-forming strengthening agent as a core layer; wherein the pore-forming strengthening agent is selected from chopped fibers, and the chopped fibers are one or a mixture of SiC fibers and carbon fibers.
[0043] In this step, after the pore-forming reinforcing agent and the coating agent are mixed, they are kept warm and stirred at a temperature of 150-240° C. for 10-20 hours, and then dried to obtain pore-forming reinforcing particles.
[0044] The pore-forming reinforcing agent is short-cut fibers with a diameter of 0.1-0.2 μm and a length of 1-10 μm.
[0045] The coating agent is a mixture of 50-60% epoxy resin and 40-50% polysiloxane resin in terms of volume fraction.
[0046] Wherein, the shell thickness of the pore-forming and strengthening particles is 0.05-0.1 μm.
[0047] The epoxy resin has a viscosity of 1-50 cp and a molecular weight of 350-8000. Its molecular structure is as follows:
[0048]
[0049] The viscosity of the polysiloxane resin is 1-50cp and the molecular weight is 350-8000. Its molecular structure is as follows:
[0050]
[0051] Here, there are two main types of choices for the side chains R1 and R2: one is a linear branch, such as methyl, propyl, isopropyl; the other is a non-linear branch, such as cyclopropyl, cycloethyl, benzene ring, etc.
[0052] The step of preparing hot-pressed ceramic core slurry is as follows: a mixed powder and a plasticizer are mixed to obtain a hot-pressed ceramic core slurry; wherein the mixed powder includes a skeleton powder, a filler, and the pore-forming strengthening particles.
[0053] In this step, the skeleton powder is one or two of Al2O3 and SiO2. The skeleton powder is a ceramic powder with a particle size of 35-125 μm.
[0054] The filler is one or two of ZrO2, Y2O3 and ZrSiO4. The filler is a ceramic powder with a particle size of 5-55nm.
[0055] The skeleton powder, filler and coated pore-forming reinforcing agent are mixed and mechanically stirred for 2-3 hours to obtain a mixed powder.
[0056] In addition, in the steps of preparing pore-forming strengthening particles and preparing hot-pressed ceramic core slurry, the raw materials used, in parts by weight, include: 60-80 parts by weight of skeleton powder; 5-15 parts by weight of filler; 5-15 parts by weight of pore-forming strengthening particles; and 10-20 parts by weight of plasticizer.
[0057] The step of injection molding is to perform injection molding on the hot-pressed ceramic core slurry to obtain a hot-pressed ceramic core wet blank.
[0058] Among them, in this step: setting injection molding parameters, injection molding the hot injection ceramic core slurry through injection molding equipment, and obtaining the hot injection ceramic core wet blank.
[0059] The injection molding parameters are set as follows: injection pressure is 2-4 MPa, and pressure is maintained for 10-30 seconds.
[0060] Degreasing and sintering steps: degreasing and sintering the hot-pressed ceramic core wet blank to obtain a hot-pressed ceramic core.
[0061] Among them, in the degreasing and sintering steps: in the degreasing treatment: the temperature of the degreasing treatment is 400-600°C, and the time of the degreasing treatment is 120-180min; preferably, the heating rate is 1-5°C / min, and the cooling rate is 1-5°C / min.
[0062] Preferably, in the sintering process, the sintering temperature is 1300-1500°C, and the sintering time is 180-300min; preferably, the heating rate is 2-8°C / min, and the cooling rate is 2-8°C / min.
[0063] Here, regarding the above scheme, it is necessary to explain:
[0064] 1) The present invention introduces chopped fibers into the raw materials for preparing hot-pressed ceramic cores as pore-forming and reinforcing phases, thereby increasing the core open porosity through the supporting effect of the fibers on the matrix powder and improving the core bending strength through the bridging effect of the fibers.
[0065] 2) The present invention coats the surface of the chopped fibers before adding them, which can significantly improve the uniformity of the chopped fibers in the core slurry. At the same time, the coated surface layer can sinter and react with the core matrix powder during the core sintering process, thereby promoting the improvement of the core's bending strength while inhibiting the carbonization of the fibers during the sintering process.
[0066] 3) The chopped fibers added in the present invention can provide a channel for the overflow of the plasticizer during the degreasing process, promote the decomposition of the plasticizer, improve the degreasing efficiency of the core, and reduce cracks and defects in the core caused by degreasing.
[0067] The present invention is further described below by way of examples:
[0068] Example 1
[0069] This embodiment prepares a hot-pressed ceramic core, wherein the raw materials used are as follows: 65 parts by weight of skeleton powder, 10 parts by weight of filler, 5 parts by weight of pore-forming strengthening particles, and 20 parts by weight of plasticizer (16 parts by weight of paraffin wax and 4 parts by weight of beeswax). The skeleton powder is Al2O3 powder with a particle size of 80 μm and SiO2 powder with a particle size of 50 μm, mixed in a ratio of 3:1. The filler is ZrO2 powder with a particle size of 20 nm. The pore-forming strengthening agent is chopped SiC fiber with a diameter of 0.1 μm and a length of 10 μm.
[0070] The preparation method mainly comprises the following steps:
[0071] 1) SiC fiber was added to a mixture of 60 mL of epoxy resin with a viscosity of 10 cp and a molecular weight of 1000 and 40 mL of polysilicon carbolic acid resin with a viscosity of 40 cp and a molecular weight of 7500, and the mixture was stirred at 180° C. for 16 h. After drying, pore-forming reinforced particles were obtained.
[0072] The shell thickness of the pore-forming and strengthening particles prepared in this embodiment is 0.05-0.1 μm.
[0073] The structural diagram of the pore-forming strengthening particles prepared in this embodiment is shown in Figure 3 As shown. Figure 3 As shown, a shell layer 2 (coating agent) is coated on the outside of a core layer 1 (SiC fiber).
[0074] 2) The skeleton powder, filler, and pore-forming strengthening particles are mechanically stirred and mixed for 2 hours to obtain a mixed powder; the mixed powder is added to a plasticizer, and the mixture is stirred at a temperature of 100° C. for 200 hours to obtain a hot-pressed ceramic core slurry.
[0075] 3) Setting the injection molding process parameters: the injection pressure is 3.5 MPa, and the pressure is maintained for 30 seconds, and the hot-pressed ceramic core slurry is injection molded by the injection molding equipment to obtain the hot-pressed ceramic core wet blank.
[0076] 4) Degreasing and sintering the hot-pressed ceramic core wet blank to obtain the hot-pressed ceramic core.
[0077] The degreasing treatment conditions are as follows: the heating rate and the cooling rate are both 1°C / min, the degreasing treatment temperature is 550°C, and the degreasing treatment time is 180min.
[0078] The sintering conditions are as follows: the heating rate and the cooling rate are 5°C / min, the sintering temperature is 1300°C, the sintering time is 240min, and finally a hot-pressed ceramic core is obtained.
[0079] in, Figure 2 This is a local microstructure diagram of the hot-pressed ceramic core prepared in this embodiment. It can be seen that SiC fibers are in the hot-pressed ceramic core.
[0080] Example 2
[0081] This embodiment prepares a hot-pressed ceramic core, wherein the raw materials used are as follows: 60 parts by weight of skeleton powder, 8 parts by weight of filler, 12 parts by weight of pore-forming strengthening particles, and 20 parts by weight of plasticizer (14 parts by weight of paraffin wax and 6 parts by weight of beeswax). The skeleton powder is Al2O3 powder with a particle size of 80 μm and SiO2 powder with a particle size of 120 μm, mixed in a ratio of 1:7. The filler is ZrSiO4 powder with a particle size of 10 nm. The pore-forming strengthening agent is short-cut C fiber with a diameter of 0.2 μm and a length of 3 μm.
[0082] The preparation method mainly comprises the following steps:
[0083] 1) C fiber was added to a mixture of 50 mL of epoxy resin with a viscosity of 1 cp and a molecular weight of 350 and 50 mL of polysilicon carbolic acid resin with a viscosity of 30 cp and a molecular weight of 2000, and the mixture was stirred at 200° C. for 15 h. After drying, pore-forming reinforced particles were obtained.
[0084] The shell thickness of the pore-forming and strengthening particles prepared in this embodiment is 0.05-0.1 μm.
[0085] 2) The skeleton powder, filler, and pore-forming strengthening particles are mechanically stirred and mixed for 2 hours to obtain a mixed powder; the mixed powder is added to a plasticizer, and the mixture is stirred at a temperature of 120° C. for 240 hours to obtain a hot-pressed ceramic core slurry.
[0086] 3) Setting the injection molding process parameters: the injection pressure is 4 MPa, and the pressure is maintained for 20 seconds, and the hot-pressed ceramic core slurry is injection molded by the injection molding equipment to obtain the hot-pressed ceramic core wet blank.
[0087] 4) Degreasing and sintering the hot-pressed ceramic core wet blank to obtain the hot-pressed ceramic core.
[0088] The degreasing treatment conditions are as follows: the heating rate and the cooling rate are both 5°C / min, the degreasing treatment temperature is 580°C, and the degreasing treatment time is 160min.
[0089] The sintering conditions are as follows: the heating rate and the cooling rate are 8°C / min, the sintering temperature is 1300°C, the sintering time is 260min, and finally a hot-pressed ceramic core is obtained.
[0090] Example 3
[0091] This embodiment prepares a hot-pressed ceramic core, wherein the raw materials used are as follows: 80 parts by weight of skeleton powder, 5 parts by weight of filler, 5 parts by weight of pore-forming strengthening particles, and 10 parts by weight of plasticizer (7 parts by weight of paraffin wax and 3 parts by weight of beeswax). Among them, the skeleton powder is Al2O3 powder with a particle size of 125 μm. The filler is Y2O3 with a particle size of 10 nm and ZrO2 powder with a weight ratio of 1:10. The pore-forming strengthening agent is short-cut carbon fiber with a diameter of 0.2 μm and a length of 10 μm.
[0092] The preparation method mainly comprises the following steps:
[0093] 1) Add carbon fiber to a mixture of 55 mL of epoxy resin with a viscosity of 50 cp and a molecular weight of 7800 and 45 mL of polysiloxane resin with a viscosity of 5 cp and a molecular weight of 8000, stir at 200°C for 15 hours, and obtain pore-forming reinforced particles after drying.
[0094] The shell thickness of the pore-forming and strengthening particles prepared in this embodiment is 0.05-0.1 μm.
[0095] 2) The skeleton powder, filler, and pore-forming strengthening particles are mechanically stirred and mixed for 2 hours to obtain a mixed powder; the mixed powder is added to a plasticizer, and the mixture is stirred at a temperature of 100° C. for 180 hours to obtain a hot-pressed ceramic core slurry.
[0096] 3) Setting the injection molding process parameters: the injection pressure is 3.5 MPa, and the pressure is maintained for 25 seconds, and the hot-pressed ceramic core slurry is injection molded by the injection molding equipment to obtain the hot-pressed ceramic core wet blank.
[0097] 4) Degreasing and sintering the hot-pressed ceramic core wet blank to obtain the hot-pressed ceramic core.
[0098] The degreasing treatment conditions are as follows: the heating rate and the cooling rate are both 3°C / min, the degreasing treatment temperature is 500°C, and the degreasing treatment time is 180 min.
[0099] The sintering conditions are as follows: the heating rate and the cooling rate are 6°C / min, the sintering temperature is 1450°C, the sintering time is 240min, and finally a hot-pressed ceramic core is obtained.
[0100] Comparative Example 1
[0101] Comparative Example 1: A hot-pressed ceramic core is prepared. Compared with Example 1, the pore-forming enhancer is not coated. The raw materials used are as follows: 65 parts by weight of skeleton powder, 10 parts by weight of filler, 5 parts by weight of pore-forming enhancer, and 20 parts by weight of plasticizer (16 parts by weight of paraffin wax and 4 parts by weight of beeswax). The skeleton powder is Al2O3 powder with a particle size of 80 μm and SiO2 powder with a particle size of 50 μm, mixed in a ratio of 3:1. The filler is ZrO2 powder with a particle size of 20 nm. The pore-forming enhancer is chopped SiC fiber with a diameter of 0.1 μm and a length of 10 μm.
[0102] The preparation method mainly comprises the following steps:
[0103] 1) The skeleton powder, filler and pore-forming enhancer are mechanically stirred and mixed for 2 hours to obtain a mixed powder; the mixed powder is added to a plasticizer, and the mixture is stirred at a temperature of 100° C. for 200 hours to obtain a hot pressing ceramic core slurry.
[0104] 2) Setting the injection molding process parameters: the injection pressure is 3.5 MPa, and the pressure is maintained for 30 seconds, and the hot-pressed ceramic core slurry is injection molded by the injection molding equipment to obtain the hot-pressed ceramic core wet blank.
[0105] 3) Degreasing and sintering the hot-pressed ceramic core wet blank to obtain the hot-pressed ceramic core.
[0106] The degreasing treatment conditions are as follows: the heating rate and the cooling rate are both 1°C / min, the degreasing treatment temperature is 550°C, and the degreasing treatment time is 180min.
[0107] The sintering conditions are as follows: the heating rate and the cooling rate are 5°C / min, the sintering temperature is 1300°C, the sintering time is 240min, and finally a hot-pressed ceramic core is obtained.
[0108] The performance test data of the hot-pressed ceramic cores prepared in Examples 1-3 and Comparative Example 1 are shown in Table 1.
[0109] Table 1
[0110] Test items Bending strength Open porosity Example 1 26.3MPa 39% Example 2 21.4MPa 36% Example 3 29.8MPa 32% Comparative Example 1 17.3MPa 18%
[0111] It can be seen from Table 1 that the solution of the embodiment of the present invention (ie, introducing core-shell structured pore-forming strengthening particles into the raw material) can significantly improve the bending strength and open porosity of the hot-pressed ceramic core.
[0112] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a hot-pressed ceramic core, characterized in that: It includes the following steps: The step of preparing pore-forming strengthening particles is as follows: using a coating agent and a pore-forming strengthening agent as raw materials to prepare pore-forming strengthening particles; wherein the pore-forming strengthening particles are in a core-shell structure with the coating agent as a shell layer and the pore-forming strengthening agent as a core layer; wherein the pore-forming strengthening agent is selected from chopped fibers, and the chopped fibers are one or a mixture of SiC fibers and carbon fibers; wherein the diameter of the chopped fibers is 0.1-0.2 μm and the length is 1-10 μm; and the coating agent is a mixture of 50-60% epoxy resin and 40-50% polysilicon carbane resin by volume fraction; The step of preparing hot-pressed ceramic core slurry is as follows: mixing a mixed powder and a plasticizer to obtain a hot-pressed ceramic core slurry; wherein the mixed powder comprises a skeleton powder, a filler, and the pore-forming strengthening particles; Injection molding step: performing injection molding on the hot-pressed ceramic core slurry to obtain a hot-pressed ceramic core wet blank; Degreasing and sintering steps: degreasing and sintering the wet blank of the hot-pressed ceramic core to obtain a hot-pressed ceramic core; Wherein, the shell thickness in the pore-forming strengthening particles is 0.05-0.1 μm; Wherein, in the step of preparing the pore-forming and strengthening particles: the viscosity of the epoxy resin is 1-50cp and the molecular weight is 350-8000; the viscosity of the polysiloxane resin is 1-50cp and the molecular weight is 350-8000; The raw materials for preparing the hot-pressed ceramic core slurry include, by weight: 60-80 parts by weight of skeleton powder; 5-15 parts by weight of filler; 5-15 parts by weight of pore-forming strengthening particles; 10-20 parts by weight of plasticizer; Wherein, in the sintering process: the sintering temperature is 1300-1500° C., and the sintering time is 180-300 min.
2. The method for preparing a hot-pressed ceramic core according to claim 1, characterized in that: In the step of preparing pore-forming and strengthening particles: After the pore-forming reinforcing agent and the coating agent are mixed, a first stirring treatment is performed at a temperature of 150-240° C., and after drying, pore-forming reinforcing particles with a core-shell structure are obtained.
3. The method for preparing a hot-pressed ceramic core according to claim 2, characterized in that: The first stirring treatment lasts for 10-20 hours.
4. The method for preparing a hot-pressed ceramic core according to claim 1, characterized in that: In the step of preparing the hot-pressed ceramic core slurry: The preparation step of the mixed powder includes: mixing the skeleton powder, the filler and the pore-forming strengthening particles, and then performing a second stirring process to obtain the mixed powder.
5. The method for preparing a hot-pressed ceramic core according to claim 4, characterized in that: In the step of preparing the mixed powder: the time of the second stirring treatment is 2-3 hours.
6. The method for preparing a hot-pressed ceramic core according to claim 1, characterized in that: In the step of preparing the hot-pressed ceramic core slurry: After the mixed powder and the plasticizer are mixed, a third stirring treatment is performed at a temperature of 80-120° C. to obtain a hot pressing ceramic core slurry.
7. The method for preparing a hot-pressed ceramic core according to claim 6, characterized in that: The time of the third stirring treatment is 150-240h.
8. The method for preparing a hot-pressed ceramic core according to any one of claims 1 to 7, characterized in that: The skeleton powder is one or two of Al2O3 and SiO2; and / or The filler is one or more of ZrO2, Y2O3, ZrSiO4; and / or The particle size of the skeleton powder is 35-125 μm; and / or The particle size of the filler is 5-55 nm; and / or In terms of mass fraction, the plasticizer is a mixture of 70-80% paraffin and 20-30% beeswax.
9. The method for preparing a hot-pressed ceramic core according to any one of claims 1 to 7, characterized in that: In the injection molding step, the injection molding parameters are set as follows: The injection pressure is 2-4MPa, and the pressure is maintained for 10-30s.
10. The method for preparing a hot-pressed ceramic core according to any one of claims 1 to 7, characterized in that: In the degreasing treatment, the temperature of the degreasing treatment is 400-600° C., and the time of the degreasing treatment is 120-180 minutes.
11. The method for preparing a hot-pressed ceramic core according to claim 10, characterized in that: In the degreasing treatment, the heating rate is 1-5°C / min, and the cooling rate is 1-5°C / min.
12. The method for preparing a hot-pressed ceramic core according to claim 1, characterized in that: In the sintering process, the heating rate is 2-8°C / min, and the cooling rate is 2-8°C / min.
13. A hot-pressed ceramic core, characterized in that: The hot-pressed ceramic core is prepared by the method for preparing a hot-pressed ceramic core according to any one of claims 1 to 12.
14. The hot-pressed ceramic core according to claim 13, characterized in that: The hot-pressed ceramic core has an open porosity of 25-40% and a bending strength of 18-30 MPa.
15. The hot-pressed ceramic core according to claim 13, characterized in that: The hot-pressed ceramic core has a fiber-overlapping pore structure.
